(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we study CR warped product submanifolds in locally metallic Riemannian manifolds. We provide several non-trivial examples of such submanifolds. We establish a sharp inequality known as Chen’s inequality for the squared norm of the second fundamental form. We also discuss the equality case of Chen’s inequality.